MEMBEDAH ANATOMI FIQH SIYASAH DALAM PUTUSAN MAHKAMAH KONSTITUSI TENTANG PRESIDENTIAL THRESHOLD - Muhamad Sofi Mubarok (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
The Constitutional Court sets presidential threshold as an open legal policy or open law policy for legislators. In other words, presidential threshold as stipulated in Act Number 7 of 2017 on General Elections, especially in the article 222, does not contradict to the Constitution of the Republic of Indonesia 1945 and its accordance with efforts to maintain government stability. Although this decision left two constitutional judges dissenting opinion since it was issued, the decision is relevant to the fiqh siya>sah construct concerning the need to maintain government stability through determining sufficient conditions in the selection process for the head of state. Borrowing Norman Fairclough's Critical Discourse Analysis (CDA) approach, the decision is in accordance to the fiqh siya>sah dictum for two reasons. First, there is a religious dogma which states that a head of state must come from the strongest clan through prophet tradition (al-hadis) states, al-aimmatu min-quraysyin. Second, in the fiqh siya>sah tradition, any policy can be formulated as long as the benefit of the people can be achieved. The stipulation of strict prerequisites is not intended to obstruct the right of a mukallaf to be elected as head of state, but aims to achieve other interests that are greater and benefit society, in the form of advocating for the rights of the state, ensuring a sense of security, and the realization of religious values in social life.